Nurturing Structural Thinking through Teacher-Facilitated Problem Solving - Yao, Xiangquan (Ohio Journal of School Mathematics, 2023)
One essential goal of mathematics teaching is to develop the habit of mind and the ability to look for and recognize structures, to probe into and act upon structures, and to reason and justify in terms of general structures. Framed by the five practices for orchestrating productive mathematics discussions (Smith & Stein, 2011), this paper uses the Horse Rider problem as an example to illustrate how teachers can nurture student structural thinking through careful sequencing of mathematical tasks.